Ce-modified Co–Mn oxide spinel on reduced graphene oxide and carbon black as ethanol tolerant oxygen reduction electrocatalyst in alkaline media. Issue 55 (15th December 2022) - Wolf, Sigrid; Roschger, Michaela; Genorio, Boštjan; Garstenauer, Daniel; Radić, Josip; Hacker, Viktor
Abstract : Synergistic effects from modifications of cobalt manganese oxide with Ce and use of rGO boost ethanol tolerance and ORR activity/stability. Abstract : Electrocatalyst development for alkaline direct ethanol fuel cells is of great importance. In this context we have designed and synthesized cerium-modified cobalt manganese oxide (Ce-CMO) spinels on Vulcan XC72R (VC) and on its mixture with reduced graphene oxide (rGO). The influence of Ce modification on the activity and stability of the oxygen reduction reaction (ORR) in absence and presence of ethanol was investigated. The physicochemical characterization of Ce-CMO/VC and Ce-CMO/rGO–VC reveals CeO2 deposition and Ce doping of the CMO for both samples and a dissimilar morphology with respect to the nature of the carbon material. The electrochemical results display an enhanced ORR performance caused by Ce modification of CMO resulting in highly stable active sites. The Ce-CMO composites outperformed the CMO/VC catalyst with an onset potential of 0.89 V vs. RHE, a limiting current density of approx. −3 mA cm −2 and a remaining current density of 91% after 3600 s at 0.4 V vs. RHE. In addition, remarkable ethanol tolerance and stability in ethanol containing electrolyte compared to the commercial Pt/C catalyst was evaluated. These outstanding properties highlight Ce-CMO/VC and Ce-CMO/rGO–VC as promising, selective and ethanol tolerant ORR catalysts in alkaline media.